Two case reports and a literature review of hyperphosphatasia with intellectual disability syndrome 2 caused by a PIGO mutation - Wang, Xinyi; Zhao, Jingya; Zhao, Xiaoke; Ding, Le; Zhu, Min; Li, Yang (Frontiers in Pediatrics, 2025)
ObjectiveThis study investigates the clinical features and genetic mutations associated with hyperphosphatasia with impaired intellectual development syndrome-2 (HPIDS2).MethodsA retrospective analysis was performed on two HPIDS2 cases treated at the Department of Rehabilitation, Nanjing Children's Hospital, from 2019 to 2023. Clinical features and genetic characteristics were summarized through a literature review.ResultsGenetic testing showed compound heterozygous variations in the PIGO gene for both patients (Patient 1: c.[2612A>C];[2361dup]; Patient 2: c.[2510T>A];[693C>G]), with c.[2510T>A] and c.[693C>G] identified as novel mutations.ConclusionGlobal developmental delay, with or without hyperphosphatemia, may indicate HPIDS2. The level of alkaline phosphatase elevation could reflect disease severity and prognosis. Our cases expand the known pathogenic variations in the PIGO gene and phenotypic spectrum of HPIDS2.